Differential Expressions of Proteomes of Oil Palm (Elaeis Guineensis Jacq.) and Arabidopsis Thaliana Tissues During Callogenesis - Zamri, Rozita (2010)
In in vitro propagation, callus is initiated by exposing explants to the appropriate types and concentrations of plant growth regulators, and the use of suitable medium. The efficiency of callogenesis varies from plant to plant, and is dependent on the ability of each and every key player in the particular cells or tissues to respond to the inductive stimuli. The key players in this process are active functional proteins required, and should be available on time and in the right amount for completing the process. This study focuses on differentially expressed proteins in oil palm and A. thaliana tissues during callogenesis. Micropropagation is commercially desired for cloning and multiplication of a very high yielding planting material with elite characteristics. However, oil palm micropropagation is rather a slow and inefficient process. Oil palm callogenesis rate is low in comparison to other plants. Using A. thaliana as a model plant, this study aims to discover the active candidate proteins which have the potential to trigger in vitro callogenesis. The first step in the investigation using Proteinchip®-SELDI-TOF-MS approach was to generate complete protein profiles of both plants tissues during callogenesis based on distinct morphological appearances. Ten oil palm ortets, 4 replicates each were sampled. Two hundred explants per replicate cultured, producing a total of 800 explants from each lines. A time course protein extraction and profiling were conducted at monthly intervals at month 0 (before media treatment), month 1, 2 and 3 until callus was formed at month 4 (after media treatment). At least 37 protein peaks were up-regulated when most of the explants induced callus during the fourth month. Out of the 37 proteins, 14 are differentially expressed only at callus stage. Ten replicates of A. thaliana samples were cultured. Explant development and callus induction were observed until callus was formed at 20th day. Protein profiling were conducted at five distinct developmental stages, which are at day 0 (before media treatment), day 5, day 10, day 15 and day 20 (after media treatment). Six potential up-regulated protein peaks were recognized to be present at the critical stage of callusing in A. thaliana. Differentially-expressed proteins from both oil palm and A. thaliana were compared. Six potential callogenesis protein candidates were identified. The proteins were not present in the leaf explants suggesting that they were induced as a result of in vitro callus induction.